2013
DOI: 10.1128/ec.00148-13
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Variants of Plasmodium falciparum Exhibit a Narrow Range of Rolling Velocities to Host Receptor CD36 under Dynamic Flow Conditions

Abstract: c Cytoadhesion of Plasmodium falciparum parasitized red blood cells (pRBCs) has been implicated in the virulence of malaria infection. Cytoadhesive interactions are mediated by the protein family of Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1). The PfEMP1 family is under strong antibody and binding selection, resulting in extensive sequence and size variation of the extracellular domains. Here, we investigated cytoadhesion of pRBCs to CD36, a common receptor of P. falciparum field isolates, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…However, binding behavior to CD36 is controversial. In agreement with the current study, Herricks and colleagues observed rolling adhesion of isogeneic IEs over a microfluidic slide coated with CD36 40 . Rolling adhesion was also observed over human dermal microvascular ECs, which express numerous CD36 molecules on their surface (86 ± 14 × 10 6 molecules/mm 2 ) 41 .…”
Section: Discussionsupporting
confidence: 92%
“…However, binding behavior to CD36 is controversial. In agreement with the current study, Herricks and colleagues observed rolling adhesion of isogeneic IEs over a microfluidic slide coated with CD36 40 . Rolling adhesion was also observed over human dermal microvascular ECs, which express numerous CD36 molecules on their surface (86 ± 14 × 10 6 molecules/mm 2 ) 41 .…”
Section: Discussionsupporting
confidence: 92%
“…Cytoadherence on HDMECs is mediated by CD36 and ICAM-1 (22)(23)(24), of which they have been measured to contain 86 5 14 Â 10 6 and 6 5 3 Â 10 6 molecules/mm 2 , respectively (22). However, ICAM-1 is thought to be the primary ligand for rolling, whereas CD36 supports rolling adhesion only within a narrow velocity range and is mainly considered as ligand for firm adhesion (22,24,37).…”
Section: Differential Adhesion Behavior Of Trophozoites and Schizontsmentioning
confidence: 99%
“…Cytoadherence on HDMECs is mediated by CD36 and ICAM-1 (22)(23)(24), of which they have been measured to contain 86 5 14 Â 10 6 and 6 5 3 Â 10 6 molecules/mm 2 , respectively (22). However, ICAM-1 is thought to be the primary ligand for rolling, whereas CD36 supports rolling adhesion only within a narrow velocity range and is mainly considered as ligand for firm adhesion (22,24,37). Wallshear stresses in the range from 0.03 to 0.10 Pa (corresponding to shear rates from 42 to 142 Hz) were chosen to represent the range of physiological hydrodynamic conditions under which rolling adhesion iRBCs occurs in postcapillary venules and sinusoids (68)(69)(70).…”
Section: Differential Adhesion Behavior Of Trophozoites and Schizontsmentioning
confidence: 99%
See 1 more Smart Citation
“…All are of DBLα type 0 with varying sub-classifications, a type almost exclusively associated with UPS B and C var genes 4 , concordant with our UPS typing. Similarly, the six genes analysed all contain CIDRα subtypes predicted to bind CD36, a phenotype of UPS B and C type var genes 17 . BC12a, J1a and J1d contain DBLβ5 which is predicted to mediate binding to ICAM-1 18 , 19 .…”
Section: Resultsmentioning
confidence: 99%